Opuntia dillenii: A Forgotten Plant with Promising Pharmacological Properties - Reza Shirazinia; Vafa Baradaran Rahimi; Ashrafali Rezaie Kehkhaie; Amirhossein Sahebkar; Hassan Rakhshandeh; Vahid Reza Askari (Korean Pharmacopuncture Institute, 2019)
Generative and vegetative parts of the cactuses have had a long-lasting position in folk medicine and their effects could partly be confirmed in scientific experiments. Nowadays, the cactus, fruits, and cladodes are the focus of many studies because of their desirable properties. Therefore, the summarized reports of valuable properties of medicinal plants may be a good way to familiarize researches with a new source of drugs with lower side effects and higher efficacy. Opuntia dillenii, a well-known member of the Cactaceae family, is used as a medicinal plant in various countries and grows in the desert, semi-desert, tropical and sub-tropical areas. It shows diverse pharmacological activities such as: antioxidant, anti-inflammatory, anti-tumor, neuroprotective, hepatoprotective, hypotensive etc. OD fruit also possesses valuable constitutes for instance: betalains, ascorbic acid, total phenol, protein as well as essential elements which suggest the significant potential of this plant as a complementary therapy against several pathological conditions. This review describes experimental evidence about pharmacological and therapeutic potential of OD in order to give the basis of its application in the prevention and treatment of some chronic diseases. More studies on OD can help better understanding of its pharmacological mechanism of action to explain its traditional uses and to identify its potential new therapeutic applications.